2020
DOI: 10.3390/foods9050668
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS Analysis, Antioxidant and Antimicrobial Activities of Achillea Odorata Subsp. Pectinata and Ruta Montana Essential Oils and Their Potential Use as Food Preservatives

Abstract: In order to discover new natural resources with biological properties, the chemical composition, the antioxidant and antimicrobial activities, and the potential use as food preservative of essential oils of Moroccan Achillea odorata subsp. pectinata (AOpEO) and Ruta montana (RMEO) were studied. Gas chromatography-mass spectrometry (GC-MS) analysis revealed the presence of 21 and 25 compounds in AOpEO and RMEO, respectively. The results showed that the major compounds of AOpEO are camphor (45.01%), bornyl aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 88 publications
2
39
0
Order By: Relevance
“…Essential oils are natural mixtures of volatile compounds frequently used in cosmetics, perfume, and sanitary products for both their fragrance and biological activities [4][5][6][7]. Another principal characteristic of EOs is their volatility, which limits residues after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils are natural mixtures of volatile compounds frequently used in cosmetics, perfume, and sanitary products for both their fragrance and biological activities [4][5][6][7]. Another principal characteristic of EOs is their volatility, which limits residues after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Achillea millefolium, one of Achillea species was proved to prevent biofilms formation of Staphylococcus genus bacteria, the most common cutaneous bacterial commensals 19 . Antimicrobial property of Achillea was also demonstrated by others Benali et al 20 using gas chromatography-mass spectrometry. Herman and Herman 21 reported that Achillea species were among herbal substances used for burn wounds management due to its antimicrobial effect.…”
Section: Discussionmentioning
confidence: 55%
“…Fatty acids, such as oleic acid, linoleic acid, and palmitic acid, are important sources with antimicrobial and antifungal activities [18] . The antimicrobial properties of P. major are attributed to the presence of camphor, bornyl acetate, and borneol compounds; the biological activities of these compounds have previously been investigated [49] .…”
Section: Discussionmentioning
confidence: 99%